Sublingual glyceryl trinitrate during colonoscopy and terminal ileal intubation: a randomized controlled trial. Issue 1 (February 2017) - Hill, Patsy-Anne; Panteleimonitis, Sofoklis; McKay, Graham; Watson, Carol; Prach, Andre; Macdonald, Angus
Background and aims: Sublingual glyceryl trinitrate has been used as an aid to cannulate the Sphincter of Oddi during endoscopic retrograde cholangiopancreatography. Its role in terminal ileal intubation during colonoscopy is unknown. This study examines the role of sublingual glyceryl trinitrate in terminal ileal intubation during colonoscopy. Methods: A triple-blind randomized controlled trial comparing sublingual glyceryl trinitrate (800 µg) vs. placebo (saline) in relation to terminal ileal intubation during colonoscopy was performed. Following caecal intubation, participants received sublingual glyceryl trinitrate/placebo followed by a 2-min observation period before intubation was attempted. Data on time to intubate the terminal ileum and intubation rate were collected. Results: A total of 110 patients (age: 58 years (18–75)) were recruited and randomised as per protocol: 54 received sublingual glyceryl trinitrate. Terminal ileal intubation was successful in all patients receiving sublingual glyceryl trinitrate and in 53 (94.6%) of those receiving saline ( p = 0.243: Fischer's exact). The median time taken for ileal intubation after application of spray was 72.5 (7–900) s in the glyceryl trinitrate group compared with 125 (5–900) s in the placebo group ( p = 0.150: Mann–Whitney). There were no major adverse events reported in either group. Conclusions: Terminal ileal intubation rates and timing were very good in both groups. Routine sublingual glyceryl trinitrate was not proven to be beneficial in improving terminal ileal intubation or intubation success rates in the hands of experienced colonoscopists. However, trends in this small study might suggest that glyceryl trinitrate could be useful in the hands of less experienced colonoscopists or in difficult terminal ileal intubation cases.